ANALYSIS OF FINANCIAL MANAGEMENT IN PORT BUSINESS ENTITIES KARIMUN DISTRICT - Ady Hermawan; Andre Resta Ferdian; Azman; Febrianto Rinaldi; Prihandani; Indrayani; Muammar Khaddafi (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The research aims to analyze and find out operational costs and financial performance for 2021-2022 at the Karimun Regency Port Business Entities. This study uses a quantitative descriptive approach, which is numerical data that is managed and analyzed. Data collection techniques used are observation, interviews, and documentation. As for the data analysis technique used in this study to determine operational costs used the operational cost budget formula and to determine the company's financial performance used profitability ratios, solvency ratios, liquidity ratios, and activity ratios. The results showed that the operational cost budget level was not efficient. Financial performance of the Karimun Regency Port Business Entity in 2021-2022 using profitability ratio analysis.